PERAN PIMPINAN DALAM MENINGKATKAN DISIPLIN KERJA KARYAWAN PT JASARAHARJA PUTERA PALEMBANG - Febrino Valentin; Munfaridi Munfaridi (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2016)
The purpose of this report is to determine the role of  Leader and assembling of labor discipline on PT JasaraharjaPutera Palembang. The object of the analysis of this report are employees of PT Jasaraharja Putera Palembang on the production and insurance claims department. The writer used questionnaires, interviews, and research literature in collecting data. The techniques of analyzed data used  quantitative and qualitative techniques. The result showed that the percentage of variable leader have an average score of 55.55% included in the adequate category. Discipline apply has an average percentage score of 55.76%, which is adequate. Dominant dimension of leader is on motivation, making decision and implementation of the dominant discipline dimension that remuneration and human relations. The suggestion is leader of PT Jasaraharja Putera should be able to increase the variable that is considered weak and adequate by employees of PT Jasaraharja Son. Leadership should approach the employee by provides clear information and good communication to employees, pays more attention to employees to achieve organizational goals, cares about the employee's duties as  responsibility as the leader, rebukes and punishes employees who make mistakes